Specificity models in MAPK cascade signaling - Ma, Yan; Nicolet, Jade (FEBS open bio, 2023)
The precise execution of various cellular functions relies on the maintenance of signaling specificity from input detection to cellular outputs. However, diverse signaling pathways share similar or identical intermediate components. A well‐conserved intermediate, the Mitogen‐Activated Protein Kinase (MAPK) cascade, participates in a myriad of signaling pathways, regulating signal transduction from input to output. This typifies the “hourglass conundrum”, where a multitude of inputs and outputs all operate through a limited number of common intermediates. Therefore, understanding how MAPK cascades regulate a variety of outputs with specificity is a fundamental question in biology. This review highlights four major insulating mechanisms that improve signaling specificity: selective activation, compartmentalization, combinatorial signaling, and cross‐pathway inhibition. We focus on plant pathways that share MAPK cascade components and compare mechanisms with those of animals and yeast. We hope this conceptual overview will aid future studies to better understand plant signaling specificity. Diverse signaling pathways share similar or identical intermediate components. The MAPK cascade is a well‐conserved intermediate, participating in myriad signaling pathways. The precise execution of various cellular functions relies on signaling specificity from input detection to cellular outputs. Comparing plant and animal pathways, this review highlights four major insulating mechanisms that improve signaling specificity.